#TITLE_ALTERNATIVE# - TIARA PUTRA (NIM : 103 09 004); Pembimbing : Dr. Rer. Nat. M. Ikbal Arifyanto, ARI
Stellar stream is a group of stars moving with the same velocity and direction (O. J. Eggen, 1996). Helmi & White (1999) states that stellar stream of Galactic halo are the remnants of accreted satellites. It supports hierarchical merging scenario where galaxies are formed of an attracted material surrounding proto system and join up into a larger structure. There are several methods for finding streams of stars in the halo, as an example of a Helmi & White (1999) Ã‚Â– Helmi & de Zeeuw (2000) method, Klement et al (2009) method, or Arifyanto & Fuchs (2005) method. The search strategy stellar stream is by looking over densities in phase space. In this final project will be compared the search methods of stream from Helmi & White (1999) Ã‚Â– Helmi & de Zeeuw (2000) method and Klement et al (2009). They used a different parameter for Integral of Motion. For Helmi & White (1999) Ã‚Â– Helmi & de Zeeuw (2000) uses the energy E, the angular momentum L and the zcomponent Lz for Integral of Motion. As for Klement et al (2009) using the parameters of velocity dispersion and angular orbit (Vaz, VΔE, υ). By studying about stellar stream, we can learn more about the origins of the formation of galaxies.